Dynamic spectrum sharing a game theoretical overview. - Zhu Ji (IEEE Communications magazine)
In order to fully utilize the scarce spectrum resources, with the development of cognitive radio technologies, dynamic spectrum sharing becomes a promising approach to increase the efficiency of spectrum usage. Game theoretical dynamic spectrum sharing has been extensively studied for more flexible, efficient, and fair spectrum usage through analyzing the intelligent behaviors of network users equipped with cognitive radio devices. This article provides a game theoretical overview of dynamic spectrum sharing from several aspects: analysis of network users' behaviors, efficient dynamic distributed design, and optimality analysis.